Synthesis of ethanolic and aqueous extracts of sponge gourd peels and their application for the prevention of mild steel corrosion in saline water - Jaiswal A.; Bhardwaj S.; Rai S.; Pandey I.; Ji G. (My University, 2025)
Natural and waste materials could be a successful and economical strategy for saving metals from corrosion because they could easily exchange electrons with the metals through their biomolecules. This work reported the use of waste sponge gourd peels (SGP) for the suppression of mild steel (MS) loss after dipping in 0.5 M NaCl. The water and ethanolic extracts of sponge gourd peels (SGPAE and SGPEE) had been prepared and characterized by Fourier transform infrared spectroscopy (FTIR). Both extracts were found to be loaded with biomolecules. SGPAE was used as an inhibitor, and SGPEE was utilized as a coating. Different concentrations (50–300 mg L−1) of SGPAE were added to 0.5 M NaCl, and SGPEE layers (1–5) were deposited on MS via drop casting and then exposed to salty water. The corrosion testing had been performed by open circuit potential (OCP) monitoring, Tafel polarization curves (TC), electrochemical impedance spectroscopy (EIS), field ion emission scanning electron microscopy (FESEM), energy dispersive X-ray spectra (EDX), and atomic force microscopy (AFM). The testing had shown that both extracts were effective against MS corrosion. SGPAE had shown maximum inhibition at 200 mg L−1 (75%), and SGPEE had shown maximum protection of 83% for 4 layers. The cause of MS protection by SGP was claimed to be the coverage of MS by the adsorbed molecules (SGPAE) or thin barrier layers of molecules (SGPEE). The reason for protection was also explained through an illustration. © 2023 Informa UK Limited, trading as Taylor & Francis Group.